PENGARUH PELAKSANAAN ETIKA PROFESI TERHADAP PENGAMBILAN KEPUTUSAN AKUNTAN PUBLIK (AUDITOR) - Hery (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The main purpose of this research is to find out: (1) in how far public accountant have understood about the implementation of professional ethics, and (2) how influence the implementation of professional ethics toward public accountant's decision making that can be accounted for. That method was adopted to Collect data was based on survey method and convenience sampling. Primary data was taken from closed questionnaire, taken from 85 public accountant. The Scale measurement using the method of Likert's scale on five points. Data then was analysed statistically (quantitative) by used one-sample test and regression aquation to prove the truth of hypothesis. The result of analysis shows that public accountant mostly have understood about the implementation of professional ethics. Generally, according to Sonny Keraf (1998) : a professional person is a person that is always doing activities (work) by refer to professional ethics.Keywords : professional ethics, decision making, public accountant